An evolutionary game study of environmental regulation strategies for marine ecological governance in China - Gao, Lehua; Yan, An; Yin, Qiaorong (Frontiers in Marine Science, 2022)
The choice of environmental regulation strategies for marine ecological pollution governance is vital for China’s promotion of collaborative marine ecological management. First, based on the assumption of limited rationality, we established a three-party evolutionary game model of China’s central government, local governments, and marine enterprises from the perspective of environmental policy to explore the dynamic evolution process of the game strategies of the three participants and the stability of the system equilibrium point. Second, we used numerical simulations to investigate how the incentive- and penalty-based policies of central and local governments have different effects on local governments and marine enterprises, respectively. Finally, we introduced a reputation loss model of public participation to explore the game strategy choices of the three parties under public participation. The finding reveal that (1) Local governments are more sensitive to the central government’s punishment policies than marine enterprises are. (2) Increasing the punishment of local governments on enterprises can simultaneously enhance the willingness of enterprises to govern and the willingness of local governments to implement. Moreover, the local governments policy of punishing enterprises was more direct and effective than that of the central government. (3) Although local governments subsidies for marine enterprises can increase their probability of governing marine ecology, they can also decrease local governments' willingness to implement. Finally, (4) Public participation can quickly promote the active governance of marine enterprises. Accordingly, the suggestions are proposed to maintain China's marine ecological security, e.g., the central government should focus on urging local governments to strictly implement marine environmental protection policies; local governments should take the lead in supervising and guiding marine enterprises; and all levels of government need to take measures to promote public participation in marine ecological governance.